Endotoxin aggression in athletes: etiological factor analysis - Oparina, O. N.; Pashin, A. A.; Toma, J. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the etiological factors of influence on a sport-specific endotoxin aggression.